BUSINESS PERFORMANCE OF 15 LARGEST EXPORTERS IN FOOD-PROCESSING INDUSTRY IN THE PERIOD 2008-2014 - Jeremić, Zoran B.; Milojević, Marko; Terzić, Ivica (Economics of Agriculture, 2016)
Agricultural export in Serbia is dominated by primary agricultural products with highly processed products having only 20% share in total exports. Low share of the processed agricultural products in total exports provides an opportunity to increase export and change its structure towards higher value-added products. In order for it to happen, the food-processing industry focused on processing domestic agricultural products needs further development. In this paper, we have analysed business performance of 15 largest exporters in the food-processing industry with the aim to get insight into their export competitiveness. The paper concludes that these companies are large net exporters that provide high added value to the countrys economy. However, business performance of the exporters under analysis are not satisfactory and their export competitiveness needs the improving. According to projections, the upcoming period will bring the most diffcult challenges for the sugar-producing companies while the fruit-processing sector has the best long-term potential for export growth.